2015
DOI: 10.3945/jn.114.205724
|View full text |Cite
|
Sign up to set email alerts
|

Fathers That Are Born Small Program Alterations in the Next-Generation Preimplantation Rat Embryos ,

Abstract: The findings from this study clearly indicate that male rat offspring born small, arising from uteroplacental insufficiency, have physiologic alterations that manifest as modifications in gene expression levels and nutrient metabolism of F2 blastocysts, even in the absence of overt cellular growth differences. These data demonstrate that growth restriction and associated disease risk have the capacity to be transmitted to the next generation of offspring via the male germ line and is manifest as early as the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 67 publications
3
7
0
Order By: Relevance
“…Along the same lines, Skjaerven et al 13 showed that daughters of pre-eclamptic mothers demonstrated an almost two-fold higher risk of developing pre-eclampsia compared with pregnancies fathered by sons of pre-eclamptic women. These findings are in line with experimental data suggesting that placenta-mediated diseases (mainly SGA and pre-eclampsia) are associated with genetic or epigenetic modifications that can be transmitted to the following generations via the maternal germ-cell line, an altered in-utero environment or by maternal mitochondrial DNA 10,15,[25][26][27] .…”
Section: Figuresupporting
confidence: 89%
“…Along the same lines, Skjaerven et al 13 showed that daughters of pre-eclamptic mothers demonstrated an almost two-fold higher risk of developing pre-eclampsia compared with pregnancies fathered by sons of pre-eclamptic women. These findings are in line with experimental data suggesting that placenta-mediated diseases (mainly SGA and pre-eclampsia) are associated with genetic or epigenetic modifications that can be transmitted to the following generations via the maternal germ-cell line, an altered in-utero environment or by maternal mitochondrial DNA 10,15,[25][26][27] .…”
Section: Figuresupporting
confidence: 89%
“…Cell counts were not different between sexes and were also similar to counts from Wistar rat embryos obtained at a similar time point [41]. Investigation of TE differentiation using culture of in vivo-derived embryos also showed no changes to outgrowth rate, number of trophoblasts, P-TGCs, ploidy or expression of TS and trophoblast differentiation markers.…”
Section: Discussionsupporting
confidence: 53%
“…We have published that preimplantation blastocysts derived from fathers born small are altered, highlighting a potential pathway to F2 offspring deficits and dysfunction (Master et al . ). Ng et al .…”
Section: Introductionmentioning
confidence: 97%